1996
DOI: 10.1007/pl00014260
|View full text |Cite
|
Sign up to set email alerts
|

Care of the adult with phenylketonuria

Abstract: Forty-three adults with classical phenylketonuria were identified by neonatal screening and treated with a phenylalanine (Phe) restricted diet. Nineteen have remained on dietary treatment with varying levels of blood Phe control and 24 have discontinued the diet at an average age of 7.8 years. Follow up at an average age of 22 years revealed that the cohort remaining on dietary treatment have achieved substantially better social and academic achievement than the 24 who discontinued dietary treatment. Another g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…Several studies have found a deterioration in intellect once the diet is discontinued (6,7,8), and some centers around the world are recommending a "diet for life" (9). Several studies have found a deterioration in intellect once the diet is discontinued (6,7,8), and some centers around the world are recommending a "diet for life" (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found a deterioration in intellect once the diet is discontinued (6,7,8), and some centers around the world are recommending a "diet for life" (9). Several studies have found a deterioration in intellect once the diet is discontinued (6,7,8), and some centers around the world are recommending a "diet for life" (9).…”
Section: Discussionmentioning
confidence: 99%
“…His blood screening showed vitamin Β12 at 236 pg/ml (normal range 180-914), iron 48 microgram/dl (59-158) and folic acid 3.93 ngr/ml (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). His blood screening showed vitamin Β12 at 236 pg/ml (normal range 180-914), iron 48 microgram/dl (59-158) and folic acid 3.93 ngr/ml (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Case Reportmentioning
confidence: 99%
“…Os requerimentos dos demais nutrientes seguem os padrões para indiví-duos normais, estabelecidos para cada faixa etária pela FAO/WHO [10] e representam a base para o cálculo e formulação da dieta dos pacientes fenilcetonúricos. A manutenção desta dieta especial, mesmo durante a vida adulta, é sugerida por diversos pesquisadores, e tem sido assunto de intensos debates na literatura [8,11,13,19,24,33]. Mas, atualmente, recomenda-se a continuidade do tratamento pela vida inteira, conforme documento elaborado por especialistas, baseado exclusivamente em evidências científicas, publicado em outubro de 2000 pelo NIH (National Institute of Health) [26].…”
Section: -Introduçãounclassified
“…7,14,62 Adolescentes fenilcetonúricos com idades entre 15 a 19 anos que abandonaram a dieta precocemente geralmente apresentam níveis de Phe entre 1300 mmol/L a 1.500 µmol/L, tendo como conseqüências mais freqüentes complicações no desenvolvimento emocional, baixa performance escolar e intelectual. 79 Koch et al 43 (1996) avaliaram 43 adultos identificados com PKU clássica desde o nascimento e tratados com dieta restrita em Phe. Observou-se que os indiví-duos que seguem com severidade a dietoterapia apresentam melhor percepção, são mais estáveis emocionalmente, possuem maior energia, maior desenvolvimento intelectual e maior maturidade social.…”
Section: Wwwfspuspbr/rspunclassified